Faktor-Faktor yang Mempengaruhi Kejadian BBLR RSUD Dr. Soedarso Pontianak - Marlenywati Marlenywati; Didik Hariyadi; Fitri Ichtiyati (Jurnal Vokasi Kesehatan, 2015)
Abstract: Hb Levels As The Dominant Factor Of Low Birth Weight Baby At dr. Soedarso General Hospital Of Pontianak. This study was aimed at figuring out the factors affecting Low Birth Weight Babies (LBW) incidence at dr. Soedarso general hospital of Pontianak. An observational method with secondary data and a cross-sectional approach were carried out in this study. The samples were 150 mothers who gave birth to dr. Soedarso general hospital of Pontianak. The statistical test used was logistic regression method with the validity level of 95%. The study revealed that there were correlation of hemoglobin level (p= 0,000; OR= 39,727), age (p= 0,000; OR= 5,333), parity (p= 0,0002; OR 8,067), pregnancy spacing (p= 0,032; OR= 3,036), weight gain (p= 0,000; OR= 16,724), antenatal care(p= 0,014; OR= 3,345) , and low birth weight babies. The dominant factor was hemoglobin (p= 0,000; exp (B) 19,924).Abstrak: Faktor-Faktor Yang Mempengaruhi Kejadian BBLR RSUD Dr. Soedarso Pontianak. Tujuan penelitian yaitu untuk mengetahui faktor-faktor yang mempengaruhi kejadian BBLR di RSUD Dr.Soedarso Pontianak. Jenis penelitian ini adalah observasional menggunakan data sekunder dengan pendekatan cross-sectional. Besar sampel yaitu 150 ibu bersalin yang melahirkan di RSUD Dr.Soedarso Pontianak. Uji statitistik menggunakan metode regresi logistik ganda dengan tingkat kepercayaan 95%. Hasil penelitian ini didapat bahwa ada hubungan antara kadar hemoglobin (p= 0,000; OR= 39,727), usia (p=0,000; OR= 5,333), paritas (p= 0,0002; OR 8,067), jarak kehamilan (p= 0,032; OR= 3,036), kenaikan berat badan (p= 0,000; OR= 16,724), dan antenatal care (p= 0,014; OR= 3,345) dengan kejadian BBLR. Faktor yang paling dominan adalah kadar hemoglobin (p= 0,000; exp (B) 19,924).